A novel Zero-Current-Switching of leading and lagging-leg switches for full-bridge phase-shifted PWM DC-DC converter - Songboonkaew, J.; Jangwanitlert, A. (My University, 2015)
This paper presents a novel Zero-Current-Switching(ZCS) technique of the leading and lagging-leg switches. The leading-leg switches are achieved under ZCS by using an active auxiliary circuit and the lagging-leg switches are achieved under the ZCS by using a blocking capacitor voltage in primary side for decreasing the primary current. Moreover, the leading-lag switches are still achieved under the ZVS condition by using the energy of the leakage inductance. In this paper, the DC-DC full-bridge converter operation is described. Experimental results provided from a 1 kW 30 kHz prototype and validated the feasibility.
Keywords: active auxiliary circuit; full-bridge converter; phase-shift; ZCS; ZVZCS